2010
DOI: 10.1016/j.jmb.2010.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Protective Antigen Octamer in the Molecular Mechanism of Anthrax Lethal Toxin Stabilization in Plasma

Abstract: Anthrax is caused by strains of Bacillus anthracis that produce two key virulence factors, anthrax toxin (Atx) and a poly-γ-D-glutamic acid capsule. Atx is comprised of three-proteins: protective antigen (PA) and two enzymes, lethal factor (LF) and edema factor (EF). To disrupt cell function, these components must assemble into holotoxin complexes, which contain either a ring-shaped homooctameric or homoheptameric PA oligomer bound to multiple copies of either LF and/or EF, producing lethal toxin (LT), edema t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
113
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(113 citation statements)
references
References 70 publications
0
113
0
Order By: Relevance
“…S5A), and we presume structural changes observed in the D2-D4 interface (Fig. S5B) explain why PA 8 is more pH stable than PA 7 (2,10,15). Thus, interfacedisrupting D2-D4 mutations accelerate channel formation, and γ-DPGA inhibits channel formation by modulating a rate-limiting, pH-dependent barrier to channel formation.…”
Section: D2-d4 Interface Stability Defines Rate-limiting Barrier To Cmentioning
confidence: 85%
See 4 more Smart Citations
“…S5A), and we presume structural changes observed in the D2-D4 interface (Fig. S5B) explain why PA 8 is more pH stable than PA 7 (2,10,15). Thus, interfacedisrupting D2-D4 mutations accelerate channel formation, and γ-DPGA inhibits channel formation by modulating a rate-limiting, pH-dependent barrier to channel formation.…”
Section: D2-d4 Interface Stability Defines Rate-limiting Barrier To Cmentioning
confidence: 85%
“…Western blots of J774A.1 extracts following exposure to preassembled PA 7 LF 3 and unassembled LT (PA + LF) were used to determine whether PA channels formed in the presence of γ-DPGA. This assay works because the PA 7 channel is an SDS-stable complex (10,15). We found that full-length γ-DPGA, but not CapD-or HCl-hydrolyzed γ-DPGA, blocks proteolysis for monomeric PA 83 and blocks channel formation for assembled PA 7 complexes (Fig.…”
mentioning
confidence: 83%
See 3 more Smart Citations